Progressive genome‐wide introgression in agricultural Campylobacter coli. Issue 4 (20th December 2012) - Sheppard, Samuel K.; Didelot, Xavier; Jolley, Keith A.; Darling, Aaron E.; Pascoe, Ben; Meric, Guillaume; Kelly, David J.; Cody, Alison; Colles, Frances M.; Strachan, Norval J. C.; Ogden, Iain D.; Forbes, Ken; et al.
Abstract Hybridization between distantly related organisms can facilitate rapid adaptation to novel environments, but is potentially constrained by epistatic fitness interactions among cell components. The zoonotic pathogens Campylobacter coli and C. jejuni differ from each other by around 15% at the nucleotide level, corresponding to an average of nearly 40 amino acids per protein‐coding gene. Using whole genome sequencing, we show that a single C. coli lineage, which has successfully colonized an agricultural niche, has been progressively accumulating C. jejuni DNA. Members of this lineage belong to two groups, the ST‐828 and ST‐1150 clonal complexes. The ST‐1150 complex is less frequently isolated and has undergone a substantially greater amount of introgression leading to replacement of up to 23% of the C. coli core genome as well as import of novel DNA. By contrast, the more commonly isolated ST‐828 complex bacteria have 10–11% introgressed DNA, and C. jejuni and nonagricultural C. coli lineages each have <2%. Thus, the C. coli that colonize agriculture, and consequently cause most human disease, have hybrid origin, but this cross‐species exchange has so far not had a substantial impact on the gene pools of either C. jejuni or nonagricultural C. coli. These findings also indicate remarkable interchangeability of basic cellular machinery after a prolonged period of independent evolution.